Adapting to Climate Change Exploring Plant Responses and Adaptations - Brij Mohan Singh (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Climate change poses a significant threat to global ecosystems, prompting an urgent need to understand and mitigate its impacts. This study focuses on exploring plant responses and adaptations to climate change, aiming to enhance our understanding of how vegetation copes with environmental challenges. Investigating a diverse range of plant species, we examine physiological, biochemical, and morphological changes in response to altered climatic conditions.Our research reveals that plants employ a variety of adaptive strategies to thrive in the face of climate change stressors. Enhanced heat and drought tolerance